“Female face” of American diplomacy - Tetiana Klynina (Cхід, 2019)
The article deals with the place, role and presence of women in the United States diplomatic service in the 20th century at the beginning of the XXI century. It is noted that since the emergence of such a term as "diplomacy" in the life of America (in fact, from 1787) and until 1922, when women were given the right to vote and, as a consequence, the right to take the exam to work in the diplomatic service, no the woman did not hold even the lowest post. The only way to get involved in diplomatic relations is to be a shadow woman behind the back of a male diplomat. From 1922, women began to gradually master the basics of the diplomatic service, but met with many obstacles in their path, one of which was the reluctance of the main executive body in international relations, the State Department, to promote women in diplomatic service. To this end, potential candidates were pre-designed to "scare" situations that a woman might encounter while performing her job. However, those who eventually succeeded in the diplomatic service performed mostly clerical duties and could not speak of the possibility of occupying some senior position in the "men's club" of the diplomatic service. It was believed that the appointment of a female ambassador abroad would damage the image of the United States on the world stage. It was not until the end of World War II, when America itself set certain rules and, as a result of production necessity, did the number of women in diplomatic service begin to increase gradually every decade, reaching its climax during the reigns of Bill Clinton and Barack Obama, who, by the time the representation of women in the State Department was not lost. It was during their reign that the highest position in the US State Department was held by women. The article provides statistics on the number of female ambassadors under US presidents, ranging from F. Roosevelt to Obama.